2019
DOI: 10.48550/arxiv.1911.04731
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Data-Free Point Cloud Network for 3D Face Recognition

Ziyu Zhang,
Feipeng Da,
Yi Yu

Abstract: Point clouds-based Networks have achieved great attention in 3D object classification, segmentation and indoor scene semantic parsing. In terms of face recognition, 3D face recognition method which directly consume point clouds as input is still under study. Two main factors account for this: One is how to get discriminative face representations from 3D point clouds using deep network; the other is the lack of large 3D training dataset. To address these problems, a data-free 3D face recognition method is propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The easiest is to rotate and crop existing face data. Another popular approach is to use 3D morphable facial models (3DMM) [50] to generate new shapes and expressions to synthesize new facial data [51,52]. Randomly selecting sub-feature sets from different samples of a person and combining them to generate a new face is also a reliable way to enrich the identities in datasets [42].…”
Section: Data Augmentationmentioning
confidence: 99%
“…The easiest is to rotate and crop existing face data. Another popular approach is to use 3D morphable facial models (3DMM) [50] to generate new shapes and expressions to synthesize new facial data [51,52]. Randomly selecting sub-feature sets from different samples of a person and combining them to generate a new face is also a reliable way to enrich the identities in datasets [42].…”
Section: Data Augmentationmentioning
confidence: 99%
“…The experiments showed that this method achieves very competitive face recognition performance. Authors in [18] proposed a data-free method for 3D face recognition using generated data from Gaussian Process Morphable Models (GPMM). Authors in [19] used the meshDOG as a detector to capture the local information of the face surface.…”
Section: Related Workmentioning
confidence: 99%
“…Zheng et al (2019) proposed an end-to-end face recognition system combining the geometric invariants, histogram of oriented gradients and the fine-tuned ResNet. Zhang et al (2019) used a PointNet++ like network to extract face feature directly from point clouds. These methods usually require the design of a complex Deep Network or CNN, and also require laborious fine tune to obtain satisfying experimental results.…”
Section: Related Workmentioning
confidence: 99%
“…Theoretically, poor data/image quality in training data set such as occlusion/data loss will lower the performance of their method. Other approaches based on deep network/deep learn such asZhang et al (2019);Zheng et al (2019) andGilani et al (2018) are very popular in recently. Thanks to the advantages of deep network technique, these methods achieve promising results in face recognition.…”
mentioning
confidence: 99%